Reasons for late attendance of pregnant women at the antenatal care at the Révélation Health Center, Kinshasa, Democratic Republic of the Congo - Jean Doudou Kitengie Kankieza; Nestor Ngoyi Kankieza; Marie-Claire Omanyondo Ohambe; Augustin Kadiata Bukasa (Orapuh, Inc., 2024)
Introduction Pregnancy is a physiological phenomenon, but it carries increased health risks for both the woman and the unborn child, in terms of morbidity and mortality. The objectives of pregnancy monitoring are to promote normal pregnancies and to identify and prevent possible complications. Purpose This study aimes to identify the reasons for late attendance at Antenatal Care (ANC) by pregnant women at the Révélation Health Center, Commune of Kisenso, City of Kinshasa, Democratic Republic of the Congo. Methods This is a descriptive, cross-sectional, and analytical study conducted at the Révélation Health Center, located in the Commune of Kisenso, City of Kinshasa, Democratic Republic of the Congo. The sample size was 35 pregnant women selected according to inclusion criteria, who provided data through a questionnaire. Data were analyzed using SPSS version 22.0 software. Results Analysis revealed that late attendance at prenatal consultations was motivated by the absence of complications during pregnancy (51.4%), financial difficulties (45.7%), professional occupation (28.6%), negligence (25.7%), and lack of decision-making power due to cultural practices (37.1%). Conclusion Strengthening awareness among women and their husbands about the importance of early and regular ANC is crucial. Effective measures to increase attendance and reduce delays include community education and involvement.